2021
DOI: 10.3390/nu13051522
|View full text |Cite
|
Sign up to set email alerts
|

Higher Branched-Chain Amino Acid Intake Is Associated with Handgrip Strength among Korean Older Adults

Abstract: Sarcopenia is a disease of old age characterized by decreased muscle mass and strength. Branched-chain amino acids (BCAAs) promote muscle mass synthesis and increase muscle strength. We aimed to develop a dietary amino acid database and to examine the association between BCAA intake and handgrip strength in Korean older adults. Data from the Korea National Health and Nutrition Examination Survey 2014–2018 were used. Overall, 4852 participants aged ≥65 years were included in the study. Demographic, lifestyle, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…Chae et al [ 30 ] observed a positive and significant correlation between leucine intake and muscle mass index in healthy middle-aged non-obese individuals (50–64 years). Similar results were observed in an older cohort (>65 years), with a significant correlation between leucine intake and handgrip strength [ 31 ]. Besides corroborating with previous reports, our results expand the literature by showing the importance of leucine intake for muscle mass in individuals above 65 years.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Chae et al [ 30 ] observed a positive and significant correlation between leucine intake and muscle mass index in healthy middle-aged non-obese individuals (50–64 years). Similar results were observed in an older cohort (>65 years), with a significant correlation between leucine intake and handgrip strength [ 31 ]. Besides corroborating with previous reports, our results expand the literature by showing the importance of leucine intake for muscle mass in individuals above 65 years.…”
Section: Discussionsupporting
confidence: 86%
“…Based on appealing acute findings of leucine supplementation, observational data analyses have investigated the protective effects of habitual leucine intake on morphological and functional outcomes during aging [ 30 , 31 ]. Chae et al [ 30 ] observed a positive and significant correlation between leucine intake and muscle mass index in healthy middle-aged non-obese individuals (50–64 years).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that the masticatory discomfort attributable to tooth loss affects the nutritional status, owing to improper dietary habits [12]. In addition, previous studies have reported that the consumption of branched-chain amino acids is associated with handgrip strength [32]. Hence, the direct or indirect effect of tooth loss on physical strength can explain this association with handgrip strength to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the EAAs, which are not synthesized in the body, are known to stimulate muscle synthesis [ 7 , 8 , 26 , 27 , 28 ] by activating the mammalian/mechanistic target of rapamycin complex 1 pathway [ 29 ]. Many studies have attempted to investigate the association between specific EAAs and muscle strength [ 30 , 31 , 32 ]. However, supplementing only a specific amino acid may induce absorption competition between amino acids that results in an imbalance of amino acids [ 33 ].…”
Section: Discussionmentioning
confidence: 99%